STRATEGI PEMASARAN USAHA DONAT MADU PASCA PANDEMI: MARKET DEFENSIF ATAU OFENSIF? - Noveri Maulana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2023)
This study aims to design the right marketing strategy for one of the national donut companies, Donat Madu Cihanjuang (DMC) based in Bandung using the analytical framework of market-based management. The study used mix-method approach by integrating qualitative and quantitative data. There are 300 respondents in the quantitative study, and 10 Interviews were also conducted with the top management. From the analysis, it is known that DMC is in an unattractive market with weak strength, bad environment, but good access of supply chain. DMC is strong in differentiation and cost strategy, but weak in marketing activities. DMC needs to take an offensive strategy to increase its market share in the industry. Several marketing strategies are needed to achieve this goal such as maintaining halal and healthy slogans, reforming the packaging and visual branding, and also adjusting to the millennial and gen-z segments by using social media more dynamically.